Place of effective management - who calls the shots? - Du Toit, Jaco M (My University, 2016)
Where Contracting States to a Double Taxation Agreement (DTA) refer to their respective domestic law concepts in respect of determining residence for purposes of a DTA, conflicting results may arise which can lead to double taxation and Contracting States being denied treaty relief. The interpretation of the concept of ‘Place of Effective Management’ as found in the residency tie-breaker clause in Art 4(3) of DTAs (based on the OECD Model Tax Convention on Income and Capital) used to resolve issues of dual-resident companies for purposes of applying the DTA, provides a pertinent example of a need for a common international understanding of treaty terms in order to avoid such potential conflicts. This paper explores how the term ‘Place of Effective Management’ should be interpreted in the above context by a South African court of law in order to conform to an internationally accepted meaning of the phrase.
A research report submitted to the faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation). Johannesburg - March, 2015
Keywords: Resident; Double taxation agreement; OECD; Central management and control; Interpretation of statutes